2017
DOI: 10.1016/j.je.2016.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Impact of birth weight on adult-onset diabetes mellitus in relation to current body mass index: The Japan Nurses' Health Study

Abstract: BackgroundAlthough birth weight is considered as a fetal determinant of the development of adult-onset diabetes mellitus (DM), its public health importance relative to adult body mass index (BMI) remains unclear. We aimed to examine the association between adult-onset DM and birth weight in relation to adult BMI.MethodsWe conducted a self-administered questionnaire as a baseline survey of the Japanese Nurses' Health Study cohort between 2001 and 2007. Exclusion criteria were applied to the volunteer sample of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 14 publications
1
33
0
Order By: Relevance
“…There is firm evidence, mostly from Western countries, that intrauterine growth restriction is associated with an increased risk of adult‐onset diabetes. We recently confirmed a similar association among the same Japanese female large‐scale cohort. That previous report showed that even among women with normal low BMI (18.5–20.9), the prevalence of adult‐onset diabetes was significantly higher in women with a low birthweight, which was consistent with the independent negative effect of birthweight shown in our path analysis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…There is firm evidence, mostly from Western countries, that intrauterine growth restriction is associated with an increased risk of adult‐onset diabetes. We recently confirmed a similar association among the same Japanese female large‐scale cohort. That previous report showed that even among women with normal low BMI (18.5–20.9), the prevalence of adult‐onset diabetes was significantly higher in women with a low birthweight, which was consistent with the independent negative effect of birthweight shown in our path analysis.…”
Section: Discussionsupporting
confidence: 90%
“…Although adult obesity is an established risk factor for type 2 diabetes, accumulating evidence shows that bodyweight at earlier life stages might also plays a role. Low birthweight has been associated with an increased risk of adult type 2 diabetes, and this association has recently been confirmed in a Japanese large‐scale female cohort, too. The risk might be further amplified by rapid catch‐up weight gain in childhood.…”
Section: Introductionmentioning
confidence: 78%
“…Finally, it has been suggested that fetal programing also operates in term SGA babies, 18 predisposing them to a higher incidence of metabolic syndrome. Another recent large cohort study 19…”
Section: Long-term Consequencesmentioning
confidence: 99%
“…Upon stratification, the association remained only significant for those cases (n ¼ 560) with EFW <10th centile (RR, 1.96; 95% CI, 1.21e3. 19). The effect of SGA on adverse outcome was significantly modified by the presence of low growth velocity, to a greater extent than by the presence of abnormal umbilical or uterine Doppler velocimetry.…”
Section: Optimal Gestational Age For Screeningmentioning
confidence: 99%
“…After screening, 21 studies (19 cohort articles) entered the meta‐analysis (Table S2), including 1 041 879 individuals and 35 699 cases of T2DM. There were 12 studies in Europe, 5 in America, and 4 in Asia (Table ). Two studies focused on females and males; three studies only focused on males, and four studies only focused on females .…”
Section: Resultsmentioning
confidence: 99%